Dynamics of Architecture in Late Baroque Rome. Cardinal Pietro Ottoboni at the Cancelleria - Olszewski, Edward (De Gruyter, 2015)
This is the first study to characterize the architectural patronage of Cardinal Pietro Ottoboni (1667-1740), and to identify twelve architects during his half century of patronage in his Ecclesiastical court of the Cancelleria. Most eminent among them were Filippo Juvarra and Domenico Gregorini. Commercial and private theaters in the palace are located from archival data, room measurements, drawings, diary accounts, Correspondence of the French Academy, and palimpsests of architectural details. The size, shape, appearance, capacity, and location of Filippo Juvarra's theater are discussed. Archival documents are cited to reveal why, how, and when it vanished. Detailed analysis is devoted to Juvarra's stage construction with its elaborate sets and moving apparatus. In his official function as Vice-Chancellor of the Church, it is well known that Ottoboni was positioned as a major patron of music, theater, and painting in late Baroque Rome. He was a librettist for oratorios performed by his resident composer, Arcangelo Corelli, and by Alessandro Scarlatti in venues in the palace, and in his basilica of San Lorenzo in Damaso, located in the palace grounds. His resident painters included Francesco Trevisani and Sebastiano Conca. He completed the construction of Bernini's Confessione in the nave of his basilica. As the sponsor of the Arcadian Academy, Ottoboni dictated taste in Roman cultural circles. His involvement in the competition for the façade of St. John Lateran is amplified. A grand overview is provided for the cardinal's commission of devotional machine constructed to rival the Lenten carnivals. As ephemeral constructions, and normally ignored liturgical phenomena, these are explored in detail for the first time. Edward J. Olszewski, Case Western Reserve University, Cleveland, Ohio, U.S.A.